Концепція кримінально-правової протидії корупції в Україні - Бондаренко, О. С. (My University, 2021)
У дисертації наведено теоретичне узагальнення й запропоновано нове вирішення наукової проблеми, яке полягало у розробленні на основі аналізу існуючих наукових підходів, чинного вітчизняного та зарубіжного законодавства і практики їх реалізації комплексної науково та практично обґрунтованої концепції кримінально-правової протидії корупції в Україні, що спиралася б на галузевий підхід. Об‘єктом дослідження є суспільні відносини, що виникають у процесі протидії корупції в Україні. Предметом дослідження є концепція кримінальноправової протидії корупції в Україні. Висвітлено генезис наукового та легального розвитку поняття «корупція» з античних часів до сьогодення. Проаналізовано окремі ключові наукові праці присвячені корупції, як негативному соціально-економічному явищу, та проблемі протидії корупції на всіх рівнях і напрямах, розслідуванню корупційних діянь. Установлено, що важливим елементом успіху наукового дослідження є вибір правильної методології, що повністю забезпечить комплексність і системність дослідження та дозволить б розробити такі висновки й рекомендації, які дійсно матимуть вагоме значення для наукової та практичної діяльності. Наголошено, що явище корупції є надзвичайно складним, так само як і поняття, що позначає це явище. Виділено основні аспекти формування поняття «корупція»: історичний, міжнародний, зарубіжний, легальний та доктринальний. Обґрунтовано, що поняття «корупція» є міждисциплінарним та широковживаним, оскільки досліджується не лише фахівцями в галузі права, а й соціології, політології, економіки, 3 державного управління та психології. Досліджено передумови появи поняття «кримінальне правопорушення» та наголошено на доцільності доповнення антикорупційного законодавства поняттям «корупційне кримінальне правопорушення». Ґрунтовно проаналізовано ознаки корупційного кримінального правопорушення. Виділено кілька підстав для класифікації корупційних кримінальних правопорушень: за видом родового об‘єкта за організацією групування у тексті примітки до ст. 45 КК України, за повнотою ознак корупційності, за предмет, за суб‘єктом, за метою, за підслідністю. Доведено необхідність криміналізації трьох адміністративних правопорушень, що пов‘язані з корупцією. По-перше, порушення встановлених законом обмежень щодо одержання подарунків. Подруге, порушення вимог щодо запобігання та врегулювання конфлікту інтересів. По-третє, невжиття заходів щодо протидії корупції. З‘ясовано, що з огляду на значущість завдання з протидії корупції держава розробила розгалужену та відносно замкнену систему спеціалізованих антикорупційних органів. Водночас певні стратегічні повноваження у сфері протидії корупції зберегли й органи загальної компетенції (Верховна Рада України, Президент України, Кабінет Міністрів України). Більше того, певні антикорупційні компетентності набули мало не всі органи державної влади та місцевого самоврядування. Надано визначення, названо ознаки та види політичної корупції, а також охарактеризовано сутність економічної корупції. Проаналізовано заходи запобігання корупції у залежності від моделі її розвитку: європейської (Фінляндія, Норвегія), азійської (Японія, Сінгапур), англо-американської (США, Канада). З числа проаналізованих заходів обрано окремі, які можуть бути запозичені у вітчизняне правозастосування. Запропоновано виділити чотири підходи до обрання покарань за корупційні кримінальні правопорушення: м‘який (Швеція, Данія), помірний (Великобританія, ФРН), суворий (Італія) та особливо суворий (США, КНР). Обґрунтовано, що корупція є глобальною проблемою людства. Тому, контроль над рівнем корупції є завданням всієї світової спільноти. Основна акумуляція зусиль у антикорупційній сфері відбувається в рамках міжнародних організацій. З‘ясовано, що міжнародне співробітництво у сфері протидії корупції реалізується Україною шляхом укладання конвенцій та угод, а також реалізації положень які містять рекомендації щодо ефективної протидії корупції. The thesis provides a theoretical generalization and offers a new solution to the scientific problem. This problem is to develop based on existing scientific approaches analysis, current domestic and foreign legislation, and practice of implementing a comprehensive, scientifically, and practically defensible concept of the criminal legal fight against corruption in Ukraine based on a branching approach. The object of the thesis is public relations that arise in the process of combating corruption in Ukraine. The subject of the thes is concept of criminal-legal counteraction of corruption in Ukraine. The genesis of the scientific and legal development of the notion of "corruption" from ancient times to the present is highlighted. Some vital scientific works were analyzed on corruption as a negative socio-economic phenomenon, the problem of combating corruption at all levels and areas, and the investigation of corruption. It was established that an essential element of the success of scientific research is the choice of the correct methodology, which would fully ensure the complexity and systematization of study and would develop such conclusions and recommendations that will be important for scientific and practical activities. It was emphasized that the phenomenon of corruption is highly complex and the notion that denotes this phenomenon. The main aspects of forming the notion of "corruption" were highlighted: historical, international, foreign, legal, and doctrinal. It is substantiated that the concept of "corruption" is interdisciplinary and widely used, as it is studied not only by specialists in the field of law, but also by sociology, political science, economics, public administration and psychology. It was proposed to classify corruption on the following grounds: the pace of development, areas of implementation, frequency, sustainability, level of organization and spread of corruption, sectoral orientation, the form of expression. The essence of the concept of "anti-corruption, " a symbiotic combination of prevention and control, is described. Emphasis is placed on the justification of the position on the identification of combating corruption and anti-corruption policy. The nature of anti-corruption principles has been formed and revealed. It is proposed to divide the principles of anti-corruption into general, i.e. specific to all branches of law, and special, which are specific only to anti-corruption activities and due to its specifics. The preconditions for the emergence of the notion of "criminal offense" were studied. The practicality of supplementing the anti-corruption legislation with the notion of "corruption criminal offense" was emphasized. The signs of a criminal corruption offense are thoroughly analyzed. It was found that, given the importance of the task of combating corruption, the state has developed an extensive and relatively closed system of specialized anticorruption bodies. At the same time, certain strategic powers in the field of anticorruption were retained by bodies of general competence (the Verkhovna Rada of 8 Ukraine, the President of Ukraine, the Cabinet of Ministers of Ukraine). Moreover, almost all state and local government bodies have acquired specific anti-corruption competencies. The legal nature of mass media was described, and the main directions of their anti-corruption activity are named. The critical role of the public in combating corruption is revealed, which is because none of the anti-corruption measures will be successful if there is no public support during its implementation. It was given the definition, peculiarities, and types of political corruption and the essence of economic corruption. It was stressed that ensuring the proper level of combating political and economic corruption is a priority for the state, as it will promote economic growth, strengthen the role of state institutions and local governments, restore confidence in them and improve the country's image at the international level. It has been proven that corruption in the judiciary is a commonplace phenomenon that undermines the principles of the rule of law, the rule of law, equality before the courts, and the independence and impartiality of the administration of justice. Measures to prevent corruption depending on the model of its development were analyzed: European (Finland, Norway), Asian (Japan, Singapore), AngloAmerican (USA, Canada). From the number of analyzed measures, some were selected that can be borrowed from domestic law enforcement. It is proposed to distinguish four approaches to the choice of punishment for corruption offenses: mild (Sweden, Denmark), moderate (UK, Germany), severe (Italy), and particularly authoritarian (USA, PRC). It is substantiated that corruption is a global problem of humankind. Therefore, controlling the level of corruption is the task of the entire world community. The central accumulation of efforts in the anti-corruption sphere takes place within the framework of international organizations. It was found out that international cooperation in the field of anti-corruption is implemented in Ukraine through the conclusion of conventions and agreements and the implementation of provisions that contain recommendations for effective anti-corruption.
The concept of criminal-legal counteraction of corruption in Ukraine
Keywords: корупція; протидія корупції; корупційне кримінальне правопорушення; концепція кримінально-правової протидії; види корупції; суб’єкти, уповноважені протидіяти корупції; corruption; anti-corruption; corruption criminal offense; concept of criminal-legal counteraction; types of corruption; entities authorized to combat corruption